2010
DOI: 10.1016/j.apenergy.2009.06.017
|View full text |Cite
|
Sign up to set email alerts
|

A paper on the unsettled question of Turkish electricity market: Balancing and settlement system (Part I)

Abstract: Turkish Electricity Market Law (EML) came into force in 2001 aiming at establishing a financially strong, stable, transparent and competitive electricity market based on bilateral contracts. Also, a balancing and settlement system (BSS) was put into practice in November 2004 to create a market where uncontracted generation can be traded, and actual implementation of the BSS started on August, 1st 2006 following a 21-month virtual implementation period. However, BSS has always been criticized from its beginning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Bids and offers accepted by TEIAS are transformed into loading and deloading instructions and issued to the relevant players''. For details of discussions of the system, the reader is referred to [93,98].…”
Section: Supply and Demand Balancingmentioning
confidence: 99%
See 3 more Smart Citations
“…Bids and offers accepted by TEIAS are transformed into loading and deloading instructions and issued to the relevant players''. For details of discussions of the system, the reader is referred to [93,98].…”
Section: Supply and Demand Balancingmentioning
confidence: 99%
“…6. Erdogdu [98] provided the mechanism of the system such that ''Bid and offer prices are submitted for each settlement period (daytime, peak, night, twice a month). Until 14:30 every day, they are also required to present physical notifications covering the 24 h period between 00:00 and 24:00 h before the day physical notifications are made.…”
Section: Supply and Demand Balancingmentioning
confidence: 99%
See 2 more Smart Citations
“…4628) enacted in 2001, which initiated a comprehensive program to reform Turkish electricity market to a more competitive and liberalized structure. There has been a plethora of studies on economic effects of liberalization and restructuring in Turkish electricity market (e.g., Güneği, 2002;Özkıvrak, 2005;Ulusoy and Oguz, 2007;Bahçe and Taymaz, 2008;Bagdadioglu and Odyakmaz, 2009;Erdogdu, 2010Erdogdu, , 2011Akkemik and Oğuz, 2011;Camadan and Erten, 2011;Camadan, 2011;Camadan and Kölmek, 2013;Karahan and Toptas, 2013;Çetin, 2014;Çetinkaya, et al, 2015;Sirin and Gonul, 2016;Avci-Surucu, et al, 2016;Asan and Tasaltin, 2017). Although there are some researchers suggesting the positive effects of full liberalization shown as the increase in the efficiency and decrease in the household prices (Akkemik and Oguz, 2011), many studies have revealed the deficiencies in Turkish market reform.…”
Section: Literature Reviewmentioning
confidence: 99%